Practical Approaches and Students’ Scientific Attitude in Chemistry in Uyo Local Government Area of Akwa Ibom State, Nigeria - EDEN, Mabel Ini-Ibehe; AKPAN, Mary Uwem; NOAH, Emem Isaac (Ilorin Journal of Education, 2024)
The study investigated the effect of practical approaches and students’ scientific attitude in Chemistry in Uyo Local Government Area of Akwa Ibom State, Nigeria. The design of the study was a quasi- experimental pretest posttest non-randomized design. The population of the study consisted of all the senior secondary two (SS2) Chemistry students in the thirteen (13) public co-educational secondary schools in Uyo Local Government Area with a sample of one hundred and twenty-nine (129) senior secondary two (SS2) Chemistry students in three intact classes from three (3) public co-educational secondary schools in the study area. The instrument for data collection was the Scientific Attitude Questionnaire (SAQ) with a reliability index of 0.76 using Cronbach alpha statistics. Data obtained were analysed using mean and standard deviation and Analysis of Covariance (ANCOVA). Findings showed that students taught using hands-on activity had positive scientific attitude while virtual laboratory and expository approach group had negative scientific attitude. There was a significant effect of practical approaches on students’ scientific attitude but no significant difference and interaction effect based on gender and scientific attitude. It was recommended, among others, that the use of hands-on activity approach should be encouraged for teaching of students who will acquire positive scientific attitudes. Also, teachers of Chemistry in secondary schools should be trained on the use of hands-on activity as it will re-emphasize the need for teachers to always enrich the teaching and learning process with good practical approaches that will foster scientific attitude.